Analisis Strategi Guru dalam Mengajar Siswa Lambat Belajar atau Slow Learner di Kelas II SDN Kunciran Indah 7 - Nurfadhillah, Septy; Faziah, Siti Nur; Fauziah, Septy Nurul; Nupus, Fika Sulaehatun; Ulfi, Nurul; Fatmawati, Fatmawati; Khoiriah, Siti (MASALIQ, 2022)
This study aims to describe the teacher's strategy in teaching slow learners or slow learners in class II SDN Kunciran Indah 7. The approach used is a qualitative approach with descriptive research type. Data collection techniques using interviews, data analysis using Milles and Huberman model data analysis and documentation. The results of the study indicate that the strategies used by the teacher in teaching slow learner students include; 1) teacher's strategy in classroom management with specifications and qualifications for changes in behavior and personality of students. 2) teacher's strategy in treating slow learner students in regular classes by placing slow learner students in the front row, rotating by paying attention to student conditions. 3) the teacher's strategy in giving assignments to slow learner students. 4) the teacher's strategy in motivating slow learner students.